Implementasi Sistem Pendeteksi Premature Ventricular Contraction (PVC) Aritmia Menggunakan Metode K-NN - Sulthan Ghiffari Awdihansyah; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The condition when the heart beats early is called the Premature Ventricular Contraction (PVC) Arrhythmia. Arrhythmia PVC conditions occur in the left ventricle of the heart. Almost every human will experience PVC arrhythmia during his lifetime. Arrhythmia PVC conditions that occur in a long time span can increase the risk of heart disease that leads to death. Examination of arrhythmia PVC conditions cannot be done independently and is quite expensive. AD8232 ECG Sensor Module, LCD 16x2, and Arduino Mega Microcontroller are used to detect PVC arrhythmia conditions. The K-NN classification method is used to classify 1 heartbeat cycle signal. The results of the K-NN classification are in 2 classes, namely the